Mecanismos de degradação das fachadas ventiladas - Ana Isabel Alves de Carvalho (2018)
At a time when interest in sustainable construction and energy efficiency issues is increasing, it is becoming more and more recurrent to see recent buildings in a state of degradation which is too advanced, taking into account their lifetime. People are selling the idea that there are certain types of self-sustaining systems, which contributes to forgetting the idea that it's necessary to preserve in order not to rehabilitate. Something is not working! The ventilated facade construction system has numerous advantages over other systems. However, is this type of system as immune to degradation as they say? And the architect? Is he part of this problem? What is his role? This dissertation intends to understand what the problem is, what its causes are, analyze them and try to find answers. The work starts from an earlier investigation and gives continuity to it. In addition to collecting and compiling information on numerous buildings covered with stone slabs, in particular, information on their state of degradation, it analyzes other themes that contribute to the understanding of phenomena and are inserted in disciplinary areas that are not architecture, as is the case of geology and engineering.